Narrative foresight in technical organizations: epistemological and methodological contributions from a practice of scenario method in Argentina - María Mercedes Patrouilleau (European Journal of Futures Research, 2017)
Abstract The following paper explores the experience of narrative Foresight applied to the use of the scenario method in Argentina in the light of the contributions of critical Future Studies concerning the narrative dimension in the last years. This research is specifically focused on analyzing applications of the scenario method in an institute of technology development in Argentina (“Instituto Nacional de Tecnología Agropecuaria”) using the causal layered analysis as a method of examination and adopting the narrative Foresight approach. We analyze how the narrative approach permeates the scenario method in the process of development, thus increasing the potential usefulness and impact of the method. Moreover, we also reflect on the utility of this approach in order to increase the strategic vision of complex organizations which are shaped, to a great extent, by linear schemes of thought where the empiric dimension of reality operates with a value of truth.